PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA RIIL - Eny Kusumawati; Rina Trisnawati; Ahmad Mardalis (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
This research aims to determine the effect of corporate governance on the real earnings management, occured in companies listed in Indonesia Stock Exchange during 2006-2010 period.Corporate governance measurement used structural approach consist of the percentage ofinstitutional ownership, manajerial ownership, the proportion of the board independentcommissioner, the size of board commissioners and the existence of an audit committee. While,earnings management measurement used real approach. This study used purposive samplingmethod. These samples are 160 companies. Analysis used multiple regression analysis. Researchresults indicate that corporate governance including institutional ownership, manajerialownership,the proportion of the board independent commissioner, and the existence of an auditcommittee have effect on real earnings management. The greater the percentage of institutionalownership, managerial ownership, the proportion of board independent commissioner, and theexistence audit committee mean the greater the level of real earnings management by the company.While, the size of board commissioners do not effect on the real earnings management. Regardlessof the number of board commissioners do not effect to behavior manager to perform real earningsmanagement.Keywords: corporate governance, real earnings management, audit committee boardcommissioners.